EGB2005N - Modern Information System to Property Management - Telec, Zbigniew (Advanced Information Technologies for Management – AITM 2008, 2008)
The article presents the property management system model in Poland. This paper work was written in order to show law regulations concerning property management, system architecture and its usability. The latter part of the article explains problems connected with the data quality of the property management system.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 35, s. 158-167